2022
DOI: 10.1097/iae.0000000000003504
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular Changes in Patients With Acute Leukemia

Abstract: Purpose: To evaluate the retinal circulation in patients with active acute leukemia, to correlate the perfusion metrics with systemic laboratory values, and to assess the vascular perfusion after leukemia remission.Methods: Longitudinal study of 22 eyes from 12 patients with acute leukemia; healthy eyes were recruited as control subjects. All patients underwent optical coherence tomography angiography at baseline. Optical coherence tomography angiography was repeated in case of morphologic leukemia remission.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(47 reference statements)
3
8
0
Order By: Relevance
“…This study evaluated changes in superficial retinal perfusion in patients with AML. We found that retinal perfusion in the macular region was significantly reduced in the acute phase of the disease, except for the central subfield, in patients with AML than in individuals with healthy eyes, which is consistent with the findings of Cicinelli et al ( 18 ); they also found lower VD in the SCP adjacent to the fovea in patients with acute leukemia, with no significant change in the fovea. This change was less pronounced in the central subfield, possibly because there are fewer vessels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study evaluated changes in superficial retinal perfusion in patients with AML. We found that retinal perfusion in the macular region was significantly reduced in the acute phase of the disease, except for the central subfield, in patients with AML than in individuals with healthy eyes, which is consistent with the findings of Cicinelli et al ( 18 ); they also found lower VD in the SCP adjacent to the fovea in patients with acute leukemia, with no significant change in the fovea. This change was less pronounced in the central subfield, possibly because there are fewer vessels.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to our findings, Wechsler et al and Zhuang et al found a statistically significant association between retinal hemorrhage and thrombocytopaenia ( 16 , 17 ). A recent study of acute leukemia showed that patients with clinically visible leukemic retinopathy had higher WBC counts and fewer PLTs than did those without retinal signs ( 18 ). The sample size and classification of leukemia may be a result of differences in findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the 14 patients had ocular symptoms, and the VA was 20/20 in all eyes. The cohort overlaps with a previous paper from our group investigating retinal circulation in AL (Cicinelli et al, 2022).…”
Section: Resultsmentioning
confidence: 74%
“…OCTA, a novel noninvasive technique, was recently adopted to quantitatively measure retinal and choroidal microvasculature in different ocular and systemic diseases, such as glaucoma (27,28), age-related macular degeneration (29-31), optic neuropathies (32-35), leukemia (36), diabetic retinopathy (37)(38)(39)(40), and TAO (14,19,20,41,42), and to evaluate the severity and prognosis of these diseases. Our study showed that the macular retinal VD was significantly decreased in the ODE and NODE groups compared with the normal group.…”
Section: Discussionmentioning
confidence: 99%